1984
DOI: 10.2118/11702-pa
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Noncondensable Gas Injection on Oil Recovery by Steamflooding

Abstract: Summary A compositional steam injection simulator was used to study the effects of noncondensable gas injection on oil recovery by steam flooding. Steam flooding oil recoveries resulting from injection of various mixtures of gas and steam were investigated for both light- and heavy-oil reservoirs. The results indicate that noncondensable gas injection with steam can accelerate production significantly early in the life of a typical heavy-oil project, but the cumulative recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…K.C. Hong estimated that for the reservoir with the crude oil viscosity of 5mPa·.s, the contribution of steam distillation to the steam drive recovery was 18% [6]. Several reports on site test items of steam drive indicate that the remaining oil saturation of the steam drive region was less than 10%, the contribution of the steam distillation to the recovery was estimated at around 10% [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…K.C. Hong estimated that for the reservoir with the crude oil viscosity of 5mPa·.s, the contribution of steam distillation to the steam drive recovery was 18% [6]. Several reports on site test items of steam drive indicate that the remaining oil saturation of the steam drive region was less than 10%, the contribution of the steam distillation to the recovery was estimated at around 10% [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] The experimental and numerical simulation studies showed that NCG injection within an appropriate time could improve the oil recoveries significantly. [4][5][6][7] However, there are some disadvantages for SAGD process, such as large energy consumption, high ultimate oil steam ratio requirement, green house gas emission, and increased watercut of produced fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to apply the same procedure to the classic long-distance displacement mode steamflooding (pattern applications for instance) did not show favourable results; Hong demonstrated that for the case of noncondensible gas (10) , while Burger and Robin did the same for the case of a solvent (11) . Initially, TTH steamflooding was studied by simulation under the name of Pressure Controlled Gravity Drainage (PCGD) process in 1997 (12) .…”
Section: Introductionmentioning
confidence: 99%